Factors of Personal Acquisition of Social Status in a Small Group in a Leisure Environment - Lapshova, Nataliia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2021)
The article presents the main results of an empirical study of the factors of personal acquisition of social status in a small group in the field of leisure. Reflecting the position of the individual in the system of society, the social status of the individual is determined by the set of rights and responsibilities of the individual in the context of social ties, groups and systems. Thus, social status is a component that simultaneously affects the individual, and which, in some way, depends on the individual. Since social status is a complex and multicomponent phenomenon, it was possible to determine its socio-psychological component structure. Social status was studied through sociometric positions of respondents. The entire sample was divided into 4 groups depending on the number of elections: neglected, rejected, accepted, stars. It was found that the factors of social status in the permissive context are the acceptance of others, the psychological climate of the team, focus on the present, social approval, lack of normative behavior (conformity). Factors of social status in the working context are personal characteristics and features of group dynamics, so it should be taken into account in combination with individual psychological characteristics. Factors of each social status for separate social groups were also singled out. The social status of the individual is an important component of the social life of every person. Its main function is to organize, design, regulate and conduct groups and their members. In the leisure environment for a group of technical professional orientation, the factors of acquiring social status for certain groups are the following characteristics: neglected – group cohesion, unaccepted – socio-psychological adaptation, accepted – the tendency to affiliation, stars – acceptance of others; for the group of humanitarian professional orientation: neglected – acceptance of others, unaccepted – group cohesion, accepted – the psychological climate of the group, the stars – emotional comfort.